2021
DOI: 10.1038/s41598-021-83470-z
|View full text |Cite|
|
Sign up to set email alerts
|

Eosinophils may serve as CEA-secreting cells for allergic bronchopulmonary aspergillosis (ABPA) patients

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a condition characterized by an exaggerated response of the immune system to the fungus Aspergillus. This study aimed to assess the relationship between carcinoembryonic antigen (CEA) and eosinophils in ABPA patients. We describes a case of a 50-year-old patient who was diagnosed with ABPA presenting with high level of CEA and eosinophils. Besides,we used immunohistochemistry and immunofluorescence to identify eosinophils and CEA in sections which were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…In ABPA patients, EOS can secrete CEA, the serum level of which was significantly higher in patients with pulmonary consolidation than those without consolidation. 12 Yang et al 26 confirmed CEA positivity in eosinophils via immunostaining in lung tissues from an ABPA patient who also had elevated serum CEA and eosinophil levels, which was consistent with the result of immunofluorescence staining in bronchial tissues and nasal polyps in our present study. A previous report indicated that interleukin-5, produced by activated lymphocytes or eosinophils, could stimulate eosinophils to enhance CEACAM expression on lipid rafts.…”
Section: Discussion and Literature Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…In ABPA patients, EOS can secrete CEA, the serum level of which was significantly higher in patients with pulmonary consolidation than those without consolidation. 12 Yang et al 26 confirmed CEA positivity in eosinophils via immunostaining in lung tissues from an ABPA patient who also had elevated serum CEA and eosinophil levels, which was consistent with the result of immunofluorescence staining in bronchial tissues and nasal polyps in our present study. A previous report indicated that interleukin-5, produced by activated lymphocytes or eosinophils, could stimulate eosinophils to enhance CEACAM expression on lipid rafts.…”
Section: Discussion and Literature Reviewsupporting
confidence: 91%
“…The secretion of CEA in AHCEAS might be related to eosinophils or other cells in allergic respiratory diseases, such as hypereosinophilic syndrome and ABPA. 13 , 26 In this study, immunofluorescence indicated that CEACAM5-positive cells were co-localized with EOS in bronchial tissues and nasal polyps ( Figure 2 ). In ABPA patients, EOS can secrete CEA, the serum level of which was significantly higher in patients with pulmonary consolidation than those without consolidation.…”
Section: Discussion and Literature Reviewsupporting
confidence: 54%
“…However, patients with ABPM sometimes show a growing mass shadow with abnormal FDG accumulation and have elevated serum CEA levels. 4 , 5 Therefore, ABPM cannot be excluded based on radiographic findings or elevated tumour maker levels alone, and careful bronchoscopic and histopathological examinations are crucial for a prompt and accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy is the major differential diagnosis in cases with a growing mass on chest computed tomography, abnormal accumulation of FDG on FDG‐PET, or elevated levels of tumour markers, including CEA. However, patients with ABPM sometimes show a growing mass shadow with abnormal FDG accumulation and have elevated serum CEA levels 4,5 . Therefore, ABPM cannot be excluded based on radiographic findings or elevated tumour maker levels alone, and careful bronchoscopic and histopathological examinations are crucial for a prompt and accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the expression of CEA by eosinophils in tissues of the respiratory tract affected by ABPM was greater than the expression in normal lung tissues. It also found that serum CEA levels were positively correlated with eosinophil counts, suggesting that activated eosinophils affect the levels of CEA secretion ( 13 ). We plotted the sequential data for the serum CEA and IgE levels and the peripheral blood eosinophil counts measured over our patient's clinical course, other than the data during adjuvant chemotherapy and five months after concluding chemotherapy in order to exclude the effects of systemic corticosteroids, and found a significant correlation between her serum CEA levels and eosinophil counts (Spearman's rank correlation coefficient Rs=0.311, p=0.011, Fig.…”
Section: Discussionmentioning
confidence: 99%